Promosi Kesehatan “Sadari” Menggunakan WhatsApp pada Mahasiswi Non Kesehatan Universitas Andalas - Ayulia Fardila Sari ZA (Jurnal Kesehatan, 2021)
The number of breast cancer incidence in Sumatera Barat Province has increases. There are 303 cases in 2017, increased to 422 cases in 2018 with a death rate of 22 cases. Based on preliminary study, there are 18 of 30 female college students were aware about the effort of Breast Self Examination (BSE) to prevent breast cancer, but there are 14 students had never done BSE. The utilization of technology is needed in helping health promotion, one of them is by using Whatsapp Messenger application. The large number of whatsapp users in Indonesia can be used to promote about BSE. The purpose of this study is to measure the effectiveness of BSE health promotion through whatsapp on the variables of knowledge, behaviour, and perceived usefulness of technology in non-health female college student at Andalas University. This research is quasi experiment with non equivalent pre test post test design. The sample of the research are 58 non-health female college students from Andalas University. The intervention is carried out for 10 days and the result of data collection is analyzed using Wilcoxon test. The result of the study are there is an increase of average knowledge score, behaviour and perceived usefulness of respondents after being given BSE health promotion using whatsapp (p value <0.005). Whatsapp can be used as an effective health promotion media for college student groups. It is recommended that to take advantage of whatsapp group feature to carry out BSE health promotion in female college student. Keywords:  Health promotion, Breast Self Examintation (BSE), WhatsApp.